The Influence of Performance Appraisal System towards Job Satisfaction, Motivation, as well as Employee Performance - Agus Subekti (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
The purpose of this study is to analyze and provide a proof of the influence that the performance appraisal system has over both job satisfaction and job motivation along with its implications on the performance of employees. The research type is explanatory research. The research population is all employees of PT Pupuk Kaltim. The sample size of this research is 140 employees. The sampling technique is ladder population in proportion to the amount of population in every stratum. The data is analyzed by implementing the approach of Smart Partial Least Square (SmartPLS). The research result indicates that performance appraisal system of employee has an effect on job satisfaction. Performance appraisal system of employee has an effect on job motivation. Performance appraisal system of employee does not have an effect on employee performance. Job satisfaction has an effect on job motivation of employee. Job satisfaction does not have an effect on employee performance. Motivation has an effect on employee performance. Performance appraisal system of employee has a greater influence towards employee performance. Performance appraisal system of employee that is applied by PT Pupuk Kaltim can significantly alter the job climate within the company. KEYWORDS: Performance Appraisal System, Job Satisfaction, Job Motivation, Employee Performance